Instructional Dynamics of Muḥādaṡah: Evaluating Pedagogical Methods and Institutional Barriers in an Indonesian Pesantren - J. Sutarjo (Lingu, 2025)
Purpose – This study investigates the implementation of muḥādaṡah (Arabic conversation) instruction at Al-Muhsin Islamic Secondary School, Metro, Indonesia. Design/methods/approach – Using a descriptive qualitative approach, data were collected through participant observation, semi-structured interviews, and documentation. The study aims to evaluate the effectiveness of the curriculum, instructional methods, and the role of teaching staff. Findings – The results indicate that while the school adopts a modern pesantren curriculum, the pedagogical implementation remains traditional, relying heavily on the "Drill" (Mim-Mem) method and rote memorization. Research implications – A significant institutional barrier was identified in the form of limited technological access for female students, as the language laboratory is located on the male campus. Furthermore, the instructors—mostly recent graduates in their service year—lack formal pedagogical training. These findings imply a need for professionalizing teacher recruitment and ensuring gender equity in facility access. The study is limited by its focus on a single institutional case. It is recommended that future research explore the integration of mobile ICT tools and the implementation of teacher training programs to transition from teacher-centered to student-centered communicative learning.